Effect of forage supplementation on metabolic indicators of Hartón del Valle heifers in the Colombian Amazon - Riascos, A. R.; Reyes, J. J.; Dihigo, L.; Medina, Y.; Narvaez, J. P. (Cuban Journal of Agricultural Science, 2021)
To evaluate the effect of supplementation with forage on metabolic indicators of Hartón of Valle heifers, 12 bovine females were used. Animals consumed Brachiaria decumbens forage, which was supplemented with 2 kg. Treatments were: T1 Control (conventional supplement), T2 (supplement with 20% of T. gigantea) and T3 (supplement with 20% of P. discolor). For data processing, the theoretical assumptions of the analysis of variance and of normality of errors were tested. A design with repeated measures over time with four repetitions per treatment was used. A mixed linear model was applied, with the help of Proc MIXED and a mixed generalized linear model, with Proc GLIMMIX of SAS. There was interaction (P=0.0009) between treatments and sampling days, for cholesterol. There were no statistical differences among treatments for metabolites of urea, creatinine, triglycerides, glucose, calcium, phosphorus, magnesium, selenium and copper. However, there were differences in the sampling period. Supplementation with 20% of Piptocoma discolor and Trichanthera gigantea stabilized the values in the metabolic indicators of cholesterol. The substitution of 20% of the conventional supplement for P. discolor or T. gigantea did not affect the studied blood indicators. However, the increase of supplementation over time improved blood indicators of triglycerides, urea, creatinine and selenium. Thus, supplementation with 20% of inclusion of P. discolor maintained stable cholesterol levels and improved glucose levels in the 30 days of supplementation. Key words: native, Piptocoma discolor, blood profile